Encouraging participant embodiment during VR-assisted public speaking training improves persuasiveness and charisma and reduces anxiety in secondary school students - Valls-Ratés, Ïo; Niebuhr, Oliver; Prieto, Pilar (Frontiers in Virtual Reality, 2023)
Practicing public speaking to simulated audiences created in virtual reality (VR) environments is reported to be effective for reducing public speaking anxiety. However, little is known about whether this effect can be enhanced by encouraging the use of gestures during VR-assisted public speaking training. In the present study two groups of secondary schools underwent a three-session public speaking training program in which they delivered short speeches to VR-simulated audiences. One group was encouraged to “embody” their speeches through gesture while the other was given no instructions regarding the use of gesture. Before and after the training sessions participants underwent respectively a pre- and a post-training session, which consisted of delivering a similar short speech to a small live audience. At pre- and post-training sessions, participant levels of anxiety were self-assessed, their speech performances were rated for persuasiveness and charisma by independent raters, and their verbal output was analyzed for prosodic features and gesture rate. Results showed that both groups significantly reduced their self-assessed anxiety between the pre- and post-training sessions. Persuasiveness and charisma ratings increased for both groups, but to a significantly greater extent in the gesture-using group. However, the prosodic and gestural features analyzed showed no significant differences across groups or from pre- to post-training speeches. Thus, our results seem to indicate that encouraging the use of gesture in VR-assisted public speaking practice can help students be more charismatic and their delivery more persuasive before presenting in front of a live audience.